UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRI DI TPQ AL-MUHAJIRIN DESA KALONGAN KABUPATEN SEMARANG - Taryanto, Taryanto; Ida Zahara Adiba; Isnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the efforts made by teachers at the Al-Muhajirin TPQ in Kalongan Village, Semarang Regency, to improve students’ Quran reading skills, along with the supporting factors and obstacles. This is a field study using a descriptive qualitative approach. The subjects of this study include teachers/ustadz as primary informants, TPQ administrators, and parents as supplementary informants. Data were collected through a triangulation of methods, including observation, interviews, and documentation. The data were then analyzed using Miles and Huberman’s theory, which involves data collection, data reduction, data presentation, and data verification. The research findings indicate that the students’ proficiency in reading the Qur’an at TPQ Al-Muhajirin remains in the transitional and developmental stages, with a primary focus on improving the clarity of articulation (makharijul huruf) and the fluency of recitation (at-tartil). Teachers have implemented various initiatives, including enhancing their own competencies through correction (tashih) and instruction (talaqqi) activities. The sorogan and classical teaching techniques were also applied. Teachers also implemented collaborative learning methods such as Yanbu’a, Tilawati, and Ummi to enhance the effectiveness of learning. Additionally, teachers routinely conducted evaluations and monitoring to track the progress of students’ abilities. Supporting factors include high student motivation, teacher commitment, and a conducive learning environment. Meanwhile, inhibiting factors include variations in students’ ability levels, inconsistent attendance, and the advancement of digital technology and the use of electronic devices that divert focus from learning.